California’s Downfall: Obama’s Stimulus Funding Is a Lifeline, But What about Next Year? - Douglass, John (International Higher Education, 2011)
California's famed public higher education system is undergoing a significant redefinition, driven solely by severe budget cuts. The state's tripartite system (the University of California, the California State University, and a network of nearly 110 community colleges) faces a daunting challenges in terms of access, time-to-degree, degree production, and the morale of faculty and staff at public universities and colleges. Though, currently, no consensus or political leadership appears to solve the long-term consequences, a debate on the next logical phase of California's higher education is necessary.